LEGAL POSITIVISM IN CONSTITUTIONAL COURT DECISION 46/PUU-XIV/2016 - Ramadhan, Febriansyah (Progressive Law Review, 2020)
This paper examines the Constitutional Court Decision 46 / PUU-XIV / 2016 through the approach of the flow of legal philosophy, specifically legal positivism which resides behind decisions that reject the petition of the applicant. Tensions between the philosophical schools of law always occur, until the judges give their decisions. This decision was classified as a hard case, which was very full of paradigm disputes. The focus of the study in this study is to look at the judges' consideration with the logical positivism approach to law. This is done because the foothold that is the basis of legal arguments places several statutory regulations at the constitutional level and the law becomes the main analysis stone looking at the problems/premise of the major, where the authority adds norms not the authority of the Constitutional Court. Therefore, the formulation of the problem in this study is the identification and analysis of arguments with nuances of legal positivism in the Constitutional Court Decision 46 / PUU-XIV / 2016. The research method used is the Doctrinal / Normative Research, which is the main legal material to be examined in this study, which is the Constitutional Court Decision 46 / PUU-XIV / 2016. The type of approach, using the analytical approach (analytical approach) and philosophical approach (philosophical approach). Conclusions from this study: The flow of legal positivism with its arguments based on axiology, ontology, and epistemology dominates the judges so that the presence of the decision rejects the petition of the applicant. The flow of legal positivism comes with reasoning/logic that is very tight and closed, which makes the legislation as the main basis, thus limiting judges to conduct self-restraint, and submit it to the legislators to execute what is expected of the applicant. In addition, the issue of the principle of legality that upholds legal certainty is also the main reason for the judges who reject the decision. The tension between the flow of legal philosophy in this decision occurs, where legal positivism which originally had a theoretical tension with the flow of natural law and historical schools, also occurred where judges who had dissenting opinions based their arguments on the flow of natural law and historical schools.